Policy Learning dalam Formulasi Kebijakan Penanggulangan Kemiskinan Daerah: Insight dari Gunungkidul - Fajar Sodiq Irawan (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
Studies on policy learning in the formulation of public policies have received less attention in the era of decentralization. This article aims to discuss policy learning in the formulation of local poverty reduction policies. By taking a case study in Gunungkidul Regency, this study shows that the learning carried out is conceptual learning which changes the perspective on local poverty reduction, from problem-based to asset-based. The form of policy learning that occurs is by selective imitation, which is taking certain elements to be included in the policy and not taking it in detail to avoids political risks. This policy learning model has implications for the implementation of policies that do not explicitly create new activities, but complement existing activity programs. The policy learning process at first glance appears as an administrative process, but in essence it is very political because it involves various actors with various interests.